IRANIAN ASYOS APPELLATIVE ONOMATIC UNITS IN OGAHIY’S WORK “RIYOZU-D-DAVLA” (TAMADDUN NURI JURNALI, 2025)
The article provides a comparative analysis of onomastic units formed on the basis of Iranian names, which are found in one of the historical works of Muhammad Riza Agehi “Riyazu-d-dawla”.